POLA KOMUNIKASI KOMITE NASIONAL PEMUDA INDONESIA (KNPI) DALAM MEMBANGUN KOHESIVITAS KELOMPOK DI KOTA PEKANBARU - Syahputra, Haidar Mahdy; ", Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The purpose of this study was to determine and analyze communication patterns and the factors that influence communication patterns KNPI Pekanbaru build group cohesiveness in Pekanbaru. The method used is descriptive method with qualitative approach. Data collection techniques used in this study is observation, interview and documentation. As for the data analysis techniques dilalukan with activity data reduction / reduction of data, the data display / presentation of data, and conclusion drawing / verification. Results show communication patterns that are formed in the build group cohesiveness on KNPI Pekanbaru is a star pattern or all channels, where each member can communicate with every other member and allow the participation of members at its optimum. As for the factors that influence the communication patterns KNPI build group cohesiveness in the city of Pekanbaru is the facilities and infrastructures of communication that have not been evenly distributed, the lack of skills of members to communicate and understand the instructionsKeywords: patterns of communication, cohesiveness, KNPI